Fabrication and properties of l-arginine-doped PCL electrospun composite scaffolds; Materials Letters; Vol. 214 - Goreninsky S. I. Semen Igorevich; Bolbasov E. N. Evgeny Nikolaevich; Sudarev E. A. Evgeniy Aleksandrovich; Stankevich K. S. Ksenia Sergeevna; Anissimov Yu. G. Yuri; Golovkin A. S. Aleksey Sergeevich; Mishanin A. I.; Viknianshchuk A. N.; Filimonov V. D. Viktor Dmitrievich; Tverdokhlebov S. I. Sergei Ivanovich (2017, 2017)
Title screen